1992
DOI: 10.1007/bf03159969
|View full text |Cite
|
Sign up to set email alerts
|

The role of lipid peroxidation in the possible involvement of membrane-Bound monoamine oxidases in gamma-aminobutyric acid and glucosamine deamination in rat brain

Abstract: Incubation of rat brain synaptosomes and mitochondria with LPO inducers (Fe2+ and ascorbate) was accompanied by a decrease of deamination of serotonin (substrate of MAO-A) in mitochondria, but not in synaptosomes, with simultaneous stimulation of GABA and GLCA deamination, apparently owing to modification of catalytic properties of brain membrane-bound MAO. Oxidation of PEA (substrate of MAO-B) was insignificantly altered in both fractions. Reactions of deamination of serotonin, GABA, and GLCA (but not PEA), w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

1992
1992
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 23 publications
1
11
0
Order By: Relevance
“…The latter was apparently due to modification of catalytic properties of brain membrane-bound MAO [61]. The similar parameters of the KM rat brain taken at the height of AS demonstrated the stimulation of lipid peroxidation in brain synaptosomes and mitochondria.…”
Section: Neurochemical Investigations Of Audiogenic Seizure Pronenessmentioning
confidence: 84%
See 1 more Smart Citation
“…The latter was apparently due to modification of catalytic properties of brain membrane-bound MAO [61]. The similar parameters of the KM rat brain taken at the height of AS demonstrated the stimulation of lipid peroxidation in brain synaptosomes and mitochondria.…”
Section: Neurochemical Investigations Of Audiogenic Seizure Pronenessmentioning
confidence: 84%
“…These data suggested that appearance of GABA-deaminating activity might be the important component in the development of epileptic seizures. It was also demonstrated that this deamination was due to modification of catalytic properties of MAO [61][62][63]. The parallel data were obtained in a mouse audiogenic seizure-prone strain [DBA/2] in which the inhibition of serotonin uptake and of oxidative deamination attenuated audiogenic seizures.…”
Section: Neurochemical Investigations Of Audiogenic Seizure Pronenessmentioning
confidence: 95%
“…A study indicates the anticonvulsant and AO effects of curcumin and Nigella saliva oil in reducing OS, excitability and induction of seizures [41]. The role of lipid peroxidation was examined in the possible involvement of monamine oxidase in the epileptic rat brain [42].…”
Section: Epilepsymentioning
confidence: 99%
“…At the same time noradrenergic, dopaminergic, serotoninergic, purinergic and several other brain systems function in the aberrant way in AE prone rats. This could signify that the brain anomaly of genetic origin exists in these animals and this abnormal genetic system is expressed in the brain at the early stage of ontogeny so that the widespread pleyotropic effects of this genetic anomaly are present in many neurotransmitter systems [15][16][17][18][19][20]. In particular, the significant interstrain differences (between KM and "0" strain in the number of D1-D2 and glutamate in striatum they being less numerous in KM rats [21].…”
Section: The Brief Description Of the Ae Study At Presentmentioning
confidence: 99%